Evidence System in Sharia Economic Dispute Resolution from the Perspective of Islamic Law: A Study of Decision Number 1848/Pdt.G/2019/PA.Mks - Hidayat, Hidayat (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
This research is a literature-based study with a descriptive approach aimed at explaining the evidence in cases of Sharia economic disputes. Data was collected through documentation methods, primarily by reviewing relevant articles and books. Data analysis used the content analysis method to identify the main messages in the literature. The results of this study are as follows: (1) In civil law, the evidentiary process requires parties to present valid evidence such as documents, witnesses, confessions, oaths, and judicial presumptions, as stipulated in Article 164 HIR/284 RBG. The main principle is that judges decide based on the “preponderance of evidence” or strong enough evidence. Documentary evidence is divided into authentic deeds (created by official authorities) and private deeds (without official authorities). Understanding the types of evidence and how to use them is crucial for achieving justice in court. And (2) In Islamic jurisprudence, the plaintiff must prove their allegations, and oaths are mandatory for those who deny. Testimonies are required by the court's order, and the minimum requirement for proof is two pieces of evidence, including witnesses, which is quantitative in nature. Testimonies and other evidence are essential in ensuring the truthfulness of the Islamic legal process. Penelitian ini adalah studi kepustakaan dengan pendekatan deskriptif, bertujuan untuk menjelaskan bukti-bukti dalam kasus-kasus sengketa ekonomi syariah. Data dikumpulkan melalui metode dokumentasi, yaitu dengan mereview artikel dan buku terkait. Analisis data menggunakan metode analisis isi untuk mengidentifikasi pesan utama dalam literatur. Hasil penelitian ini adalah (1) Dalam hukum perdata, proses pembuktian mewajibkan pihak-pihak untuk menyajikan alat bukti yang sah, seperti surat, saksi, pengakuan, sumpah, dan persangkaan hakim, sesuai dengan ketentuan dalam pasal 164 HIR/284 RBG. Prinsip utamanya adalah hakim memutus berdasarkan “preponderance of evidence” atau bukti yang cukup kuat. Alat bukti surat dibagi menjadi akta otentik (dibuat oleh pejabat resmi) dan akta di bawah tangan (tanpa pejabat resmi). Pahami jenis alat bukti dan cara menggunakannya untuk mencapai keadilan di pengadilan, dan (2) Dalam hukum peradilan Islam, penuntut harus membuktikan dakwaannya, dan sumpah wajib bagi yang inkar. Kesaksian diwajibkan oleh peradilan atas perintah hakim, dan syarat minimum pembuktian adalah dua alat bukti, termasuk saksi, yang bersifat kuantitatif. Kesaksian dan alat bukti lainnya penting dalam memastikan kebenaran dalam proses hukum Islam.